Enhanced visible light photocatalytic activity of CN-codoped TiO 2 films for the degradation of microcystin-LR - Liu, G.; Han, C.; Pelaez, M.; Zhu, D.; Liao, S.; V. Likodimos; A. G. Kontos; P. Falaras; Dionysiou, D.D. (Journal of Molecular Catalysis A: Chemical, 2013)
A sol-gel method based on the self-assembly technique with a nonionic surfactant was employed to synthesize visible-light-active CNTiO2 films with rough surface for drinking water treatment. The enhancement of photocatalytic activity of CNTiO2 films on the degradation of microcystin-LR (MC-LR) was subsequently evaluated under visible light irradiation. The films were characterized by XRD, ESEM, AFM, HRTEM, UV-vis diffuse reflectance spectroscopy (DRS), FT-IR, XPS, and porosimetry analysis. The results revealed that the physicochemical properties of the films, such as BET surface area, porosity, crystallite size and pore size distribution, could be controlled by adjusting the calcination temperature. Higher surface area, smaller crystallite size, narrow pore size distribution, and very high surface roughness (360 nm) were obtained for CN-codoped TiO2 films calcined at 400 °C. DRS showed that as-prepared CNTiO2 films exhibited higher absorption in the visible light region and a red shift in the band gap transition due to CN-doping. CNTiO2 films effectively degraded MC-LR under visible light irradiation compared to the reference film. In particular, the film calcined at 400 °C showed high mechanical stability during three consecutive cycles for MC-LR degradation. The enhancement on the photocatalytic activity of the CNTiO2 films under visible light irradiation was attributed to the synergistic effects of carbon and nitrogen doping as well as the high surface roughness of the prepared films. © 2013 Elsevier B.V.